Penerapan Model View Controller (MVC) Untuk Perancangan Sistem Ruang Buku Indonesia - Maria Ulfa; Suryayusra Suryayusra; Septa Hardini (Universitas Negeri Medan, 2020)
E-commerce is an online-based sales system, which is used to expand sales and increase sales in the Indonesian Book Room CV. In terms of sales now CV Ruang Buku Indonesia has many competitors who use internet technology to make this business lag and the sales and purchase processes are less than optimal, even decreased. Things like this can cause a business to close. Based on this, the development in the sales system is made into e-commerce with a view controller model (MVC) to facilitate the operation of the online sales system. The software development model used is the waterfall model with several stages of communication, planning, modeling, construction, and deployment. This research resulted in e-commerce of Indonesian Book Room with a view controller model that aims to face competitors and increase sales.